2003
DOI: 10.1080/00986440302101
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Analysis OF H 2 S removal on CU-V-MO, CU-V, and CU-MO mixed oxides

Abstract: Kinetic studies carried out for the sorption of H 2 S in the presence and absence of hydrogen on Cu-V-Mo, Cu-V, and Cu-Mo mixed oxides gave detailed information about the reaction sequences. Formation of SO 2 even in the presence of hydrogen at the initial stages of the sorption process showed the partial reduction of the metal oxides prior to the sulfidation step. A sorption experiment carried out with Cu-Mo mixed oxide gave incomplete sulfidation of molybdenum, whereas with Cu-V mixed oxide complete sulfidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…; Yaşşyerli et al . ). If H 2 S functions as an endogenous gaseous transmitter in the crosstalk between the sulphate reduction pathway in the chloroplasts/plastids and the transcription of sulphate transporters/sulphate reducing enzymes in the nucleus, a Cu‐induced decrease in H 2 S concentration might be responsible for the observed up‐regulation of expression and activity of the sulphate transporters.…”
Section: Discussionmentioning
confidence: 97%
“…; Yaşşyerli et al . ). If H 2 S functions as an endogenous gaseous transmitter in the crosstalk between the sulphate reduction pathway in the chloroplasts/plastids and the transcription of sulphate transporters/sulphate reducing enzymes in the nucleus, a Cu‐induced decrease in H 2 S concentration might be responsible for the observed up‐regulation of expression and activity of the sulphate transporters.…”
Section: Discussionmentioning
confidence: 97%
“…SO 2 formation was not observed during sulfidation with mixed metal oxide TieFe catalyst and TiO 2 catalyst. In our previous studies, SO 2 formation in the initial stages of sulfidation was observed with single or mixed metal oxide sorbents due to contribution of lattice oxygen of metal oxide at reducing athmosphere [16,43,44]. It could be said that oxygen mobility of TieFe mixed metal oxide catalyst to form SO 2 from H 2 S is lower.…”
Section: Ti-crmentioning
confidence: 99%
“…Another possible factor could be the aggregation of nanoparticles. Larger size aggregates reduce rates of surface reactions [32,33]. At 60°C and 120°C, two liquid phases were distinguished in the spent microemulsion: one clear liquid and one cloudy foamy phase.…”
Section: Effect Of Temperaturementioning
confidence: 99%